Microwave synthesis of some N-phenylhydrazine-1-carbothioamide Schiff bases - Al-Salami, Bushra Kamil (European Journal of Chemistry, 2018)
We have synthesized and characterized a series of carbothioamide derivatived molecules, obtained by reaction of aromatic aldehyde (Anisaldehyde, 9-anthraldehyde, cinnamaldehyde, indole-3-carboxaldehyde, 1-naphthaldehyde and o-vanillin) with an equimolar amount of 4-phenylthiosemicarbazide with microwave irradiation. The synthesized compounds have been characterized by FT-IR, 1H NMR and 13C NMR spectroscopy. Quantum calculations of the physical properties, based on density functional theory method at B3LYP/6-31+G(d,p) level of theory, were performed, by means of the Gaussian 09W set of programs. The theoretical 1H NMR chemical shift results of the studied compounds have been calculated at B3LYP method and standard 6-31+G(d,p) basis set using the standard Gauge-Independent Atomic Orbital approach. The calculated values are also compared with the experimental data available for these molecules. A good linear relationship between the experimental and calculated data has been obtained.